Audit of IT Governance Diskominfo Kota Serang Using COBIT 5 - Mochamad Arie Rafli Katami; Eko Darwiyanto; Yanuar Arie Firdaus (Indonesia Journal on Computing (Indo-JC), 2020)
The existing IT governance in Department of Communication and Informatics (Diskominfo) Serang City has an obstacle. The obstacle is innovation that has not fully facilitated the day-to-day governance and operational processes. Because good IT governance will greatly support the activities of the organization in achieving the goals set by the organization's vision and mission because it requires a harmony in business strategy and IT strategy. IT Governance is also able to find new opportunities through the application of innovative technology. To find out the current level of capability in Department of Communication and Informatics Serang City, IT governance audits are needed. COBIT 5 generates profits through effective IT management and management. The Department of Communication and Informatics Serang City target ability level is level 2 (Managed Process).